Digital Trust : A Case Study of Enterprise Content Management - Maria, Abd Rahman (2016)
In an era where technology is at the very core of a society, digital archival is the sensible way for organizations to go forward with. We no longer require hardcopy data and documents and by doing away with such hardcopy administration, organizations will save storage space and do-away with the manual tracking of these documents. Digital archival and content management, allows bigger storage, cost-efficiency in managing storage (cloud, data servers, etc) and would be an easier search lookup function when required. How do organizations do away with hardcopy information and documents? How do they change the mind set and behaviours of the organization and consequently gain "Digital Trust"? This would be the essence and problem statement of my research in my project paper. It is not only the challenge in keeping up to date with technological developments but it is the ability to cope with the changes affecting an organizations eco-system and foster trust for digitization. In this research paper, I seek to explore the process of data access control, use and ethics and its value creation in enterprise content management. Is it sufficient to legitimise data access or at what level of transparency should an organization allow? The interconnection of these issues and the regulatory response which highlights some challenges that and organization would/is facing. This paper is theorizing a case study that I had experienced and references from academic literatures and white papers that surrounds the topic of digital trust and data privacy regulations and how an organization can better align with their stakeholders' interest and how they can achieve real-time accountability.